Reduction of flood risk by indigenous knowledge at Alekdiar Char of Shibalaya Upazila in Manikganj district - Hakim, Selina (BRAC University, 2013)
This dissertation is submitted in partial fulfillment of the requirements for the degree of Master in Disaster Management, 2012.